2011
DOI: 10.1021/ac200161s
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Sensing of Pyrene Metabolites 1-Hydroxypyrene and 1-Hydroxypyrene-glucuronide

Abstract: Spectroelectrochemical sensing in an optically transparent thin layer electrode (OTTLE) cell was used for detecting the polycyclic aromatic hydrocarbon (PAH) biomarkers 1-hydroxypyrene (1-pyOH) and 1-hydroxypyrene-glucuronide (1-pyOglu) in phosphate buffer and artificial urine. This approach uses selective electrochemical modulation of a fluorescence signal by sequentially oxidizing the analytes in an OTTLE cell to distinguish between their overlapping fluorescence spectra. This technique allows for complete o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…From a quantitative point of view, the most used SEC techniques are UV/Vis absorption SEC , fluorescence SEC and Raman SEC . For this reason, and taking into account the objectives of this review, these three techniques are those that will be described in more detail below.…”
Section: Whatmentioning
confidence: 99%
See 2 more Smart Citations
“…From a quantitative point of view, the most used SEC techniques are UV/Vis absorption SEC , fluorescence SEC and Raman SEC . For this reason, and taking into account the objectives of this review, these three techniques are those that will be described in more detail below.…”
Section: Whatmentioning
confidence: 99%
“…The main advantage of SEC for analysis is the electrochemical transformation of the analytes, or of other compounds that affect the analyte during an experiment, yielding a change in the optical signal during the measurement . Therefore, in PL‐SEC is not usual to obtain the excitation spectra and the emission spectra in the same experiment.…”
Section: Howmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Approximately 80% of pyrene metabolites excreted in urine are 1-PyOglu. A common approach to assess human PAH exposure is to first convert all metabolite to 1-PyOH.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Identification and profiling of metabolites of OH-PAHs are therefore of critical importance to explore and elucidate metabolic pathways of PAHs in human body. Previous studies have revealed presence of some metabolites of OH-PAHs, such as glucuronides and sulfates in human urine [37][38][39][40][41][42]. However, detailed identification and profiling of OH-PAHs metabolites in human body have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%